Rebuking Viṣṇu and reaping the rewards - Sharma, V (American Oriental Society, 2024)
This paper argues that a concept of rebuking God (bhagavannindā) existed as a prohibited act in premodern Sanskrit Brahmanical texts, with the earliest examples in medieval Vaiṣṇava narratives (in the Bhāgavata Purāṇa and Viṣṇu Purāṇa) of Vena and Śiśupāla. The concept of bhagavannindā problematizes the Bhāgavata Purāṇa rereading of the Śiśupāla story: how can someone rebuke a god (here Kṛṣṇa) and be seemingly rewarded (through sāyujya [union] with the god)? I argue that to this problem in Vaiṣṇava and epic narratives the Bhāgavata Purāṇa offers dveṣabhakti / vairānubandha (liberation through enmity or hatred) as a potential solution. Finally, through investigation of two early modern commentaries on the Mahābhārata, I argue that reading this concept of divine censure into the epics was not without tensions. The epic commentators sometimes reveal their own ambivalent readings of episodes where Kṛṣṇa is rebuked. The paper draws attention to the importance of the Bhāgavata Purāṇa as a commentary on the Mahābhārata, upon which later exegetes relied. It surveys how and why the peculiar concept of dveṣabhakti emerges in Vaiṣnava theology and presents narrative as both the source where this orthodox concept of divine censure emerges and the site where the concept is reinforced in commentary.